Translation and validation of the Hungarian Version of the infection control standardized questionnaire: a cross-sectional study - Sahar Hammoud; Faten Amer; Haitham Khatatbeh; Huda Alfatafta; Miklós Zrínyi; Béla Kocsis (BMC, 2022)
Abstract Background To our knowledge, there is currently no psychometrically validated Hungarian scale to evaluate nurses' knowledge about infection prevention and control (IPC) practices. Thus, we aim in this study to assess the validity and reliability of the infection control standardized questionnaire Hungarian version (ICSQ-H). Methods A cross-sectional, multisite study was conducted among 591 nurses in Hungary. The original ICSQ included 25 questions. First, the questionnaire was translated into Hungarian. Then, content validity was assessed by a committee of four specialists. This was done by calculating the item content validity index and scale content validity index. Afterward, structural validity was evaluated in a two-step process using principal component analysis and confirmatory factor analysis. The goodness of fit for the model was measured through fit indices. Convergent validity was assessed by calculating the average variance extracted. Additionally, discriminant validity was evaluated by computing the Spearman correlation coefficient between the factors. Finally, the interitem correlations, the corrected item-total correlations, and the internal consistency were calculated. Results The content validity of the questionnaire was established with 23 items. The final four-factor ICSQ-H including 10 items showed a good fit model. Convergent validity was met except for the alcohol-based hand rub (ABHR) factor, while discriminant validity was met for all factors. The interitem correlations and the corrected item-total correlations were met for all factors, but the internal consistency of ABHR was unsatisfactory due to the low number of items. Conclusions The results did not support the original three-factor structure of the ICSQ. However, the four-factor ICSQ-H demonstrated an adequate degree of good fit and was found to be reliable. Based on our findings, we believe that the ICSQ-H could pave the way for more research regarding nurses' IPC knowledge to be conducted in Hungary. Nevertheless, its validation among other healthcare workers is important to tailor effective interventions to enhance knowledge and awareness.